PENGARUH DIGITAL MARKETING, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MAKE OVER DI JAKARTA UTARA - Evryana Wulandari (2023)
This study aims to investigate the influence of digital marketing and product quality on the purchasing decisions of Make Over consumers in North Jakarta. The advancements in technology and the internet have transformed the marketing landscape, with digital marketing becoming a key element in company marketing strategies. On the other hand, product quality is an essential factor that influences consumer purchasing decisions. This research utilizes a quantitative approach by collecting data through an online survey questionnaire distributed to Make Over consumers in the North Jakarta area. The research sample was selected using purposive sampling method. The collected data were analyzed using multiple regression techniques to examine the relationship between independent variables (digital marketing and product quality) and the dependent variable (purchasing decisions). The results of the analysis indicate that: (1) Digital marketing has a significant positive influence on the purchasing decisions of Make Over consumers in North Jakarta. (2) Product quality also has a significant positive influence on consumer purchasing decisions. Thus, both factors play a crucial role in shaping consumer preferences when deciding to purchase Make Over products. These findings have important implications for Make Over companies and marketers in the cosmetics and beauty industry. Effective digital marketing strategies and efforts to improve product quality can enhance brand attractiveness and boost sales. Furthermore, this research can serve as a reference for future studies in the fields of marketing and consumer behavior.